SISTEM INFORMASI AKUNTANSI PADA KINERJA USAHA KECIL MENENGAH - NANIK ERMAWATI; NURUL RIZKA ARUMSARI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The performance of Small and Medium Enterprises (UKM) is the overall success achieved by SMEs, which can be seen from the increase in sales, increase in profit, increase in working capital, and increase in operating profit. It is so important the performance of UKM for the survival of UKM. Therefore, this study examines the performance of SMEs in Kudus Regency with the research population being all SMEs in Kudus Regency. The sampling technique used in this study was purposive sampling technique with a total sample of 94 respondents who can be processed. The data analysis technique used is multiple regression analysis techniques. The results showed that: 1). Understanding of accounting information, application of information systems, entrepreneurial skills do not affect the performance of SMEs, 2). Accounting knowledge has a positive effect on the performance of SMEs.